Association between serrated polyps and the risk of synchronous advanced colorectal neoplasia in average‐risk individuals. Issue 1 (22nd October 2014) - Ng, S. C.; Ching, J. Y. L.; Chan, V. C. W.; Wong, M. C. S.; Tang, R.; Wong, S.; Luk, A. K. C.; Lam, T. Y. T.; Gao, Q.; Chan, A. W. H.; Wu, J. C. Y.; Chan, F. K. L.; et al.
Summary Background Serrated polyps of the colorectum have distinct histological features and malignant potential. Aim To assess the association between the presence of serrated polyps and synchronous advanced colorectal neoplasia. Methods Among 4989 asymptomatic Chinese individuals aged 50–70 years who underwent screening colonoscopy, 281 cases with advanced neoplasia (adenoma ≥1 cm, with tubulovillous/villous histology, with high‐grade dysplasia, or invasive adenocarcinoma) were compared with 4708 controls without advanced neoplasia for age, sex, smoking history, body mass index, family history of colorectal cancer and the presence of serrated polyps. Independent predictors of advanced neoplasia were determined by multivariate logistic regression analysis. Results The prevalence of advanced neoplasia and serrated polyps (excluding small distal hyperplastic polyps) was 5.7% and 5.6%, respectively. 3.7% and 0.4% subjects had proximal and large (≥10 mm) serrated polyps, respectively. Independent predictors of synchronous advanced colorectal neoplasia were the presence of sessile serrated adenomas (OR: 4.52; 95% CI: 2.40–8.49), proximal serrated polyps (OR: 2.23, 95% CI: 1.38–3.60), large serrated polyps (OR: 59.25; 95% CI: 18.85–186.21), hyperplastic polyps (OR: 1.66; 95% CI: 1.03–2.67), three or more serrated polyps (OR: 4.86; 95% CI: 1.24–19.15) and one or more non‐advanced tubular adenomas (OR: 3.58, 95% CI: 2.59–4.96). Conclusion Detection of proximal, sessile and/or large serrated polyps at screening colonoscopy is independently associated with an increased risk for synchronous advanced neoplasia.